CROSS-LINGUISTIC INFLUENCE OF UZBEK ON ENGLISH ACADEMIC WRITING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The influence of a writer’s native language on academic writing in English remains a significant area of investigation in applied linguistics. This study explores how linguistic and rhetorical features of Uzbek shape English academic writing produced by Uzbek university students. Using a corpus of academic essays written by undergraduate students, the research analyzes grammatical structures, lexical choices, and discourse organization that reflect systematic transfer from Uzbek. The findings reveal that Uzbek academic traditions and language-specific features influence sentence complexity, cohesion strategies, argument development, and authorial stance in English texts. These influences are shown to be consistent and patterned rather than accidental. The study argues that such cross-linguistic influence should be understood as a natural cognitive process and a resource for pedagogical development. The paper concludes by emphasizing the importance of contrastive awareness and academic literacy instruction in improving English academic writing in Uzbek educational contexts.